A facile route toward hydrophilic plasmonic copper selenide nanocrystals: new perspectives for SEIRA applications. (27th July 2021) - da Silva, Jailson J.; dos Santos, Wedja M.; Fernandes, Rafael da S.; Fontes, Adriana; Santos, Beate S.; Pereira, Claudete F.; Krebs, Patrick; Mizaikoff, Boris; Pereira, Goreti; Pereira, Giovannia A. L.
Abstract : Development of versatile and efficient plasmonic nanoprobes for detection of (bio)molecules in an ultrasmall concentration, when applied as substrates in surface-enhanced infrared (SEIRA) spectroscopy. Abstract : Non-stochiometric copper selenide nanocrystals are p-type semiconductors, which present localized surface plasmon resonances (LSPRs) in the near-infrared region, which are proportional to the Cu(i ) vacancies. Here, an easy, low-cost, and environmentally friendly methodology for the one-pot aqueous colloidal synthesis of non-stoichiometric copper selenide nanocrystals (NCs) is described. The developed methodology consists in the use of CuCl and Na2 O3 Se as precursors of copper and selenium, respectively, stabilized by mercaptosuccinic acid (MSA). The best conditions for the non-stoichiometric NCs regarding Cu/stabilizer and Cu/Se molar ratios, and the initial pH, that provided the prominent plasmonic, were those with a Cu/Se molar ratio of 1 : 2 and pH 5.0, and both molar ratios of Cu/MSA used (1 : 6 and 1 : 9) with stirring for 60 min, at 90 °C, and under N2 flux. On the other hand, the nominal stoichiometric condition (Cu2− X Se, X = 0) presented a very weak LSPR behavior, suggesting lower copper vacancy defects, as expected. The obtained plasmonic NCs were characterized optically by electron absorption spectroscopy and structurally by X-ray diffractometry, transmission electron microscopy (TEM), Raman, and infrared spectroscopy (FTIR). For the best synthetic condition, the NCs produced presented a maximum absorption band at 1124 nm. TEM images for non-stoichiometric copper selenide systems showed highly crystalline and mostly spheroid particles, and a rather large size dispersion ranging from 2 to 13 nm, with a mean size of d = 8.6 ± 2.0 nm. The crystalline structure determined by the X-ray diffractometry profile for these as-prepared non-stoichiometric nanoparticles matches those observed for the Klockmannite hexagonal structure for CuSe ( X = 1) structures. Furthermore, the use of the synthesized Cu2− X Se-MSA NCs in surface-enhanced infrared absorption (SEIRA) spectroscopy promoted an effective enhancement of infrared signatures of molecules in a very low concentration, as shown in our preliminary results with standard dye molecules.